Religion and the constitution - Greenawalt, Kent 1936- (Princeton University Press, 2006)
Should members of religious sects be able to use peyote in worship? How can the law address the refusal of parents to provide medical care to their children or the refusal of doctors to perform abortions? This title presents a framework for addressing such questions that involve competing demands of fairness, liberty, and constitutional validity